Entrepreneurship in the Digital Age: Opportunities and Strategies for the Younger Generation - Nurdin, Nurdin (Visi Pencerah Nusantara, 2025)
Entrepreneurship in the digital era offers enormous opportunities for young people to start and grow their businesses. Advances in information and communication technology, particularly the internet and social media, have transformed the way businesses operate, creating opportunities for broader innovation and growth. Digital technology not only facilitates market access but also accelerates production, distribution, and marketing processes. This study aims to analyze emerging entrepreneurial opportunities in the digital era and the strategies young people can implement to capitalize on them. The method employed is a literature review, which involves collecting data from relevant scientific articles, books, research reports, and case studies. The results indicate that e-commerce, digital marketing, and the development of innovative applications and technologies are some of the key opportunities that young people can capitalize on. E-commerce enables young entrepreneurs to access global markets with relatively low capital, while digital marketing provides new avenues to reach customers through platforms like social media and search engines. Furthermore, the development of innovative applications and technologies provides opportunities to create solutions that meet evolving market needs. Key strategies to address the challenges of digital entrepreneurship include developing a personal brand, adapting to technological advancements, collaborating with others, and innovating products and services. Success in digital entrepreneurship also depends on the ability to leverage market data and trends, as well as the flexibility to adapt to rapid market changes. In conclusion, with a proper understanding of digital entrepreneurship opportunities and strategies, young people can maximize their potential and achieve success in the digital age.